Once‐daily fluticasone furoate 50 mcg in mild‐to‐moderate asthma: a 24‐week placebo‐controlled randomized trial. Issue 11 (22nd August 2014) - Busse, W. W.; Bateman, E. D.; O'Byrne, P. M.; Lötvall, J.; Woodcock, A.; Medley, H.; Forth, R.; Jacques, L.
Abstract Background Inhaled glucocorticosteroids (ICS) are the mainstay of treatment in asthma. Fluticasone furoate (FF) is a novel, once‐daily ICS asthma therapy. This study investigated the efficacy and safety of FF 50 mcg in patients with mild‐to‐moderate persistent asthma. Methods A 24‐week, multicenter, randomized, placebo‐controlled and active‐controlled, double‐blind, double‐dummy, parallel‐group phase III study. Three hundred and fifty‐one patients (aged ≥12 years; uncontrolled by non‐ICS therapy) were randomized to treatment (1 : 1 : 1) with once‐daily FF 50 mcg dosed in the evening, twice‐daily fluticasone propionate (FP) 100 mcg or placebo. The primary endpoint was change from baseline in evening trough forced expiratory volume in 1 s (FEV1) at Week 24. Secondary endpoints were change from baseline in the percentage of rescue‐free 24‐h periods (powered endpoint), change from baseline in evening and morning peak expiratory flow, change from baseline in the percentage of symptom‐free 24‐h periods and number of withdrawals due to lack of efficacy. Results Evening trough FEV1 at Week 24 was not statistically significantly increased with FF 50 mcg once‐daily (37 ml [95% CI: −55, 128]; P = 0.430), but was with FP 100 mcg twice daily (102 ml [10, 194]; P = 0.030), vs placebo. No consistent trends were observed across other endpoints, including the powered secondary endpoint. No safety concerns were raised for either active treatment. Conclusions FP 100 mcg twice daily improved evening trough FEV1 in patients with mild‐to‐moderate persistent asthma, but FF 50 mcg once daily did not demonstrate a significant effect. Secondary endpoints showed variable results. No safety concerns were identified for FF or FP.